Influence of Input‐Scrap Quality on the Environmental Impact of Secondary Steel Production. (19th May 2016) - Haupt, Melanie; Vadenbo, Carl; Zeltner, Christoph; Hellweg, Stefanie
Summary: In electric arc furnaces (EAFs), different grades of steel scrap are combined to produce the targeted carbon steel quality. The goal of this study is to assess the influence of scrap quality on the recycling process and on the final product by investigating the effect of the scrap mix composition, and other inputs, for example, preheating energy, on the electricity demand of the melting process. A large industrial data set (empirical data set of ∼20, 000 individual heats recorded during 2.5 years at a Swiss EAF site) is analyzed using linear regression. The influence of scrap grades on electricity demand are found to correlate strongly with their respective quality; specific electricity demand is up to 45% higher for low‐quality scrap than for high‐quality scrap. Given that chemical compositions of scrap grades are highly variable and often unknown, average concentrations are determined using linear regression with scrap input as the predictors and the amounts of the investigated elements in liquid steel as the dependent variable. The lowest quality (highest copper and tin concentrations) and the highest electricity demand in the EAF are found for scrap recovered from bottom ashes of municipal solid waste incineration. Although even with low‐quality scrap input steel recycling is environmentally superior to primary steel production, the optimization potential in terms of energy efficiency and resource recovery, for example, through pretreatment, seems to be substantial.